WOMEN TEACHING ANATOMY IN R. NORTH MACEDONIA - HISTORICAL BACKGROUND AND CURRENT TRENDS - Niki Matveeva; Julija Zhivadinovik Bogdanovska (Asociación Argentina de Anatomía Clínica, 2023)
The establishment of the Faculty of Medicine in 1947 as an educational, medical and research institution enabled rapid development of the health care, health service and health system in the R. North Macedonia. Short overview of the role and participation of women in the process of medical education and scientific research work in the field of anatomy in the country provides insight into the constant rise of women with a continuous upward trend of their participation in the period from the establishment of the Faculty of Medicine until today. Women participation in medicine is of crucial importance for the further  development of  educational,  scientific   and  highly specialized health care activities in our country.